LOGISTICS SUPPORT OF CSR ACTIVITIES IN THE GLOBAL SUPPLY CHAINS OF THE PHARMACEUTICAL SECTOR - Szmelter-Jarosz, Agnieszka; Osiecka-Brzeska, Katarzyna (Journal of Positive Management, 2019)
Purpose: Research paper identifies the current trends in the logistics support of the global pharmaceutical industry, including CSR activities. Research results can be a good reference point for decision-makers in the fields of logistics management. The subject matter of the paper is based mainly on the comparison of logistics practices in the area of CSR in the pharmaceutical industry supply chains. Methodology: To achieve the research goal stated for this study, two research procedures were chosen and implemented:1) documents review (triangulation of sources); 2) literature review with the use of Boolean logic and the chosen procedure, valid for socio-economic research. Findings: This paper points out that the set of methods and tools used in logistics support of the CSR activities overlap in some part the set of methods and tools for core business activity (commercial sales of medicines). Implications for practice: Research results can be a good reference point for decision-makers in the fields of logistics management and CSR of the pharmaceutical industry. Originality/value: This paper is the first about logistics support of CSR activities in the pharmaceutical industry. It shows the similarities and differences between the support of the basic, primary activities and CSR ones. It can be the basis for further theoretical and empirical research.